Autoconsumo: Tecnologias e Aplicação de Business Intelligence no Desenvolvimento de Relatórios de Execução e Qualidade, e Criação de Formulários Dinâmicos para Obra sob o desígnio do Planeamento e Controlo de Autoconsumo Fotovoltaico na EDP Comercial - João Guilherme Reis Miranda Machado (2017)
The present document focus mainly on the most recent and newly developed technologies regarding Photovoltaic Self-Consumption targeted at LV Consumers. During the internship on the Energy Company mentioned on the title, the following were the pivotal points: - Creation of Dynamic Reports aiming at the control and supervision of service quality, monitoring of outsourced companies, execution rates, temporal evolution of installation or assistance appointments and unfulfillment of scheduled installations quotas and justifications; - Development of Dynamic Forms through the supervision of the main software conception, coding and direct implementation to real-time, in-place data acquisition on a mobile app, while establishing connections to the primary data base; - Structuring and mining of Proposals and Bids submitted by potential large-scale suppliers and/or installers, respecting financial and quality-service issues; - Daily business operations: small, medium and large scale purchases to supply the installers, transportation and supervision of the company's warehouse stocks, as well as the outsourced companies'.